Analisis Perbandingan Performa Algoritme Voronoi-Based Continuous K Nearest Neighbor Dan Dijkstra Dalam Mengelola Data Berukuran Besar (Studi Kasus : Malang Raya) - Oddy Aulia Rahman Nugroho; Fatwa Ramdani; Fitra A. Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
One of the criteria in applying mobile navigation is the ability of mobile device to continuously monitor point of access from user, but in monitoring the point or the object always changes due to the movement of user. The changes occurring are known as split nodes. There is a method used to manage split nodes that is KNN search, but the performance is still not satisfactory. Another proposed method is the Voronoi Continuous K Nearest Neighbor (VCKNN) algorithm that uses the Voronoi diagram to help manage split nodes. The use of the VCKNN algorithm is supported by Dijkstra's algorithm in searching for split nodes within the Voronoi polygon. In this research will be done comparison between VCKNN and Dijkstra algorithm in managing split nodes. This is done to get algorithms that have the best performance in managing data on segmentation, runtime and split nodes. This research will take a study area of ​​Malang Raya. Selection of Malang Raya as a study area due to unstructured road network structure neat, so it can know the performance of the proposed algorithm. From this research, the results obtained using VCKNN algorithm occurs the performance improvement compared to Dijkstra's algorithm. Increased performance occurs due to the decrease in the number of split nodes produced. The decrease of split nodes that occur using the VCKNN algorithm based on the use of administrative boundaries sub-district as the interest point resulted in the decrease of split nodes by 92.4%. With the result of this research for Malang Raya road network condition, VCKNN algorithm yield satisfying result.